Effect of configuration of calyx in cowpea flowers on infestation by spotted pod borer, Maruca vitrata (Fab.) (Lepidoptera: Crambidae) - Nasiya-Beegum, A N; Subramanian, Madhu (Journal of Horticultural Sciences, 2018)
Twenty cowpea accessions were evaluated for resistance to the spotted pod borer, Maruca vitrata in the Department of Agricultural Entomology, College of Horticulture, Kerala Agricultural University, Thrissur. The calyxes of the flowers were examined and the accessions were categorized into two groups, partially free (major portion of the sepals free, the basal portion tight) and semi tight (major portion of the sepals tight, only the tip free). Significant variation was observed in terms of damage to cowpea flowers due to spotted pod borer. The highest extent of flower damage (50.39 %) was recorded in case of Bhagyalakshmy. Categorization of the different accessions on the basis of the configuration of calyx indicated that EC 100092, Palakkadanthandanpayar, TVX – 944, EC 300039, IC 20645 and IC 52110 had semi tight calyx characterized by tight sepals with tips alone being free. All these accessions had consistently low levels of infestation ranging from zero to 3.16 per cent. The accessions C – 152, Kanakamony, PKM – 1, Anaswara, IC 20431, Sreya, Hridya, Mysore local, IC 52105, Kashikanchan, Vellayani Jyothika, Malika, Bhagyalakshmy and Lola had major portion of sepals free with their basal portion tight. Hence, they were grouped as partially free. Free sepals would provide the first instar borer larvae some extent of concealment as well as enable it to bore into the flower more easily. Tight calyx, thus, could possibly have a deterrent effect on the first instar larvae entry.